2019
DOI: 10.1136/bmjopen-2019-030917
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyles and determinants of perceived health in Italian grown-up/adult congenital heart patients: a cross-sectional and pan-national survey

Abstract: ObjectivesTo provide the first epidemiological lifestyle descriptions of the Italian grown-up/adult congenital heart disease (GUCH/ACHD) population by identifying the determinants of poor perceived health status.DesignCross-sectional pan-national survey.SettingItalian GUCH/ACHD patients who were members of the Italian Association of GUCH/ACHD.Primary and secondary outcome measuresTo discuss these lifestyle descriptions through an ad hoc developed questionnaire and health perceptions (ie, mental and physical he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
10
2
Order By: Relevance
“…Finally, considering the summary scores derived from this study, we noticed that the mean score of PCS12 (mean = 45.93; SD = 10.79) was lower than the PCS12 recently reported in Italian patients with an equivalent age distribution and affected moderate or complex congenital heart diseases [PCS12 mean score = 48.69; SD PCS12 = 8.96; MCS12 mean score = 45.56; SD MCS12 = 10.99) [33]. Conversely, the mean score of MCS12 reported in this study (mean = 45.41; SD = 10.17) was similar to the one reported in adults with moderate or complex congenital heart diseases (mean = 45.56; SD = 10.99) [33].…”
Section: Plos Onecontrasting
confidence: 49%
“…Finally, considering the summary scores derived from this study, we noticed that the mean score of PCS12 (mean = 45.93; SD = 10.79) was lower than the PCS12 recently reported in Italian patients with an equivalent age distribution and affected moderate or complex congenital heart diseases [PCS12 mean score = 48.69; SD PCS12 = 8.96; MCS12 mean score = 45.56; SD MCS12 = 10.99) [33]. Conversely, the mean score of MCS12 reported in this study (mean = 45.41; SD = 10.17) was similar to the one reported in adults with moderate or complex congenital heart diseases (mean = 45.56; SD = 10.99) [33].…”
Section: Plos Onecontrasting
confidence: 49%
“…It encompasses physical component summary (PCS12), and mental component summary (MCS12) using a standardized score ranging from 0 to 100, wherein higher value indicates a more favorable health perception. According with previous research [37], it is possible to dichotomize the scores through an adequate versus an inadequate HRQoL if we consider the median split strategy [34] acknowledging that the median scores of general Italian population, clustered by different age ranges, were previously published [38]. In this study, both components showed adequate internal consistency with Cronbach's α equal to 0.699 for PCS12 and 0.687 for MCS12.…”
Section: Measurementsmentioning
confidence: 56%
“…Overall, more than 85% of children with CHD live to adulthood due to the advancements in medical and surgical treatments 7. Accordingly, literature has emphasised the need for children with CHD to have a smooth and evidence-based transition from childhood to adulthood in order to optimise their quality of life as adults, as well as to prevent health-related risks associated with individual lifestyles 8–10. Recently, it was reported that the lifestyles of Italian adults with CHD are comparable to the lifestyles of the general population, including in relation to the prevalence of unhealthy behaviours, such as smoking or recreational drug consumptions 10.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, literature has emphasised the need for children with CHD to have a smooth and evidence-based transition from childhood to adulthood in order to optimise their quality of life as adults, as well as to prevent health-related risks associated with individual lifestyles 8–10. Recently, it was reported that the lifestyles of Italian adults with CHD are comparable to the lifestyles of the general population, including in relation to the prevalence of unhealthy behaviours, such as smoking or recreational drug consumptions 10. The similarities of the unhealthy lifestyles between adults with CHD and the general population are also relevant to the challenges faced by women with CHD during pregnancy and after childbirth 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation